1998
DOI: 10.1111/j.1440-1843.1998.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased perception of airway narrowing in patients with ild asthma

Abstract: To compare the perception of airway narrowing of nonasthmatic subjects with those having wheeze or mild asthma (doctor-diagnosed), the relationship between FEV1 and breathlessness was examined in 123 subjects from a general population sample. Scores for breathlessness, using the Borg scale, were recorded before and after inhaling incremental doses of methacholine to a maximal dose of 196 mcmol or a maximum change in FEV1 of 50%. A history of asthma symptoms, including wheeze in the previous 12 months, and doct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
3
6
1
Order By: Relevance
“…We found a strong contribution to dyspnea from the change in FEV 1 , which is consistent with the large number of existing studies that show a close relationship between change in dyspnea and change in FEV 1 . [29][30][31][32] However, in contrast to previous studies, 33 we found no contribution from the change in inspiratory capacity. Instead, the change in reactance was the only other significant contributor to change in dyspnea.…”
Section: Perception Of Dyspneacontrasting
confidence: 99%
See 1 more Smart Citation
“…We found a strong contribution to dyspnea from the change in FEV 1 , which is consistent with the large number of existing studies that show a close relationship between change in dyspnea and change in FEV 1 . [29][30][31][32] However, in contrast to previous studies, 33 we found no contribution from the change in inspiratory capacity. Instead, the change in reactance was the only other significant contributor to change in dyspnea.…”
Section: Perception Of Dyspneacontrasting
confidence: 99%
“…[30][31][32] However, in the present study, the Borg scores were standardized against methacholine dose to give a measure of perception that makes no assumption about which physiological stimuli are driving the sensation of dyspnea. We found a strong contribution to dyspnea from the change in FEV 1 , which is consistent with the large number of existing studies that show a close relationship between change in dyspnea and change in FEV 1 .…”
Section: Perception Of Dyspneamentioning
confidence: 99%
“…In previous studies PS 20 FEV 1 values have been obtained by direct interpolation of the stimulus-response curve (5,16). Although the PS 20 FEV 1 values in our study were obtained indirectly from the slope and intercept values this difference in methods is unlikely to explain the difference in findings, because evidence that the stimulusresponse relationship is linear over this range (17,18) suggests that they are comparable with values obtained directly. Alternatively, these subjects were volunteers for a clinical trial of inhaled corticosteroid and were recruited on the basis of symptom frequency, so there may have been some self-selection bias in favor of subjects with enhanced perception of symptoms.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies on both children and adults have shown that individual ability to perceive airway obstruction induced by bronchial provocation tests or occurring spontaneously varies substantially (2,13,14). Some asthmatics may consider themselves symptom-free in the midst of an asthma attack or feel severe breathlessness during a mild exacerbation.…”
Section: Discussionmentioning
confidence: 99%